Evaluation of the antiulcerogenic activity of Atriplex undulata D. Dietr. on stomachs of mice under stress and administered with indomethacin (Veterinary Science, 2020)
Hospitalized patients suffering from inflammatory processes accompanied by pain are frequently administered with NSAIDs and also, prophylactically, with gastric antisecretors. These significantly reduce gastric lesions, but also produce side effects. With the objective of looking for compounds that replace the use of these gastric protectors, in this work the antiulcerogenic activity of hydroalcoholic extracts of Atriplex undulata was evaluated. The tests were carried out using four groups of mice: the Control Group (GC) and the Controlled Control Group (GTZ) were subjected to stress due to hypothermia and immobilization, the mice belonging to the Indomethacin Control Groups (GCI) and the Control Group Treated Indomethacin (GTZI) were subjected to stress and were also administered with indomethacin. The GTZ and GTZI respectively received an oral dose of hydroalcoholic extract from 0.5 g of dried plant, resuspended in carboxymethyl cellulose. Gastric damage was assessed by measuring the ulcerated area with an image analyzer and comparing the GC with respect to the GTZ and the GCI with respect to the GTZI. In both cases, the hydroalcoholic extract significantly prevented (p≤0.05) the formation of ulcers. These results allowed us to conclude that the hydroalcoholic extract of Atriplex undulata significantly reduces the formation of stress ulcers in mice and also those induced by stress and administered at the same time with indomethacin. In future studies, clinical trials will be conducted to evaluate the potential use of drugs made from Atriplex undulata as gastric protectors during prolonged treatment with NSAIDs in animals under stress.
Keywords: Gastroprotector; Atriplex undulata; NSAIDs; Antiulcerogenic